Accuracy comparison of a mechanistic method and computational fluid dynamics (CFD) for greenhouse inner temperature predictions - Rico Garcia , E.=700 1 Castañeda Miranda, R.; Garcia Escalante, J.J.; Lara Herrera, A.
(En, Es)
Ilus., 15 ref.
Keywords: PRONOSTICO DEL TIEMPO; TEMPERATURA; INVERNADEROS; FACTORES CLIMATICOS; VENTILACION; BALANCE DE ENERGIA; MEXICO; DINAMICA DE FLUIDOS COMPUTARIZADA